ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RAYIO (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2014) - Lestari, Destry Sarasati Jingga; M Chabachib, M Chabachib (Faculty of Economics and Business Diponegoro University, 2016)
This research was conducted to examine the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Return On Asset (ROA), Firm Size and Growth Opportunity to the Deviden Payout Ratio (DPR) on companies listed on Bursa Efek Indonesia (BEI) for the period 2010 to 2014. The sampling technique used is pusposive sampling and the number of samples used for as many as 26 companies. Data obtained from the publication of Indonesia Stock Exchange (IDX ) 2010 – 2014. The analysis technique used is multiple regression analysis. The results showed that the DER and CR have no significant effect on the Dividend Payout Ratio. While the ROA and Firm Size has a significant effect on the Dividend Payout Ratio with a positive direction. Meanwhile, the growth opportunity has a significant effect on the Dividend Payout Ratio with the negative direction. From Adjusted R Square value of 0.603 indicates that there are independent variables in the model can explain the variation the DPR by 60,3%, while 39,7% variation explained by the Dividend Payout Ratio of other variables outside the model.